Penerapan Komunikasi Terapeutik untuk Mengurangi Kecemasan pada Pasien dengan Penyakit Jantung Koroner Selama Prosedur Kateterisasi di RSUD Arifin Achmad - Perdana, Nung; Suci Amin; Rahmaniza; Redho , Ahmad (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Objective: To analyze the effect of therapeutic communication on anxiety of patients with coronary heart disease (CHD) undergoing catheterization procedures at RSUD Arifin Achmad Pekanbaru Methods: This study used a quasi-experimental design with a nonequivalent control group approach. A total of 40 respondents were divided into two groups: an experimental group that was given therapeutic communication and a control group that was not. Anxiety levels were measured using the Hamilton Rating Scale of Anxiety (HRS-A) questionnaire before and after the intervention. Data were analyzed using paired t-test and independent t-test. Results The results showed a significant decrease in anxiety levels in the experimental group after therapeutic communication (p-value = 0.000). In contrast, there was no significant change in the control group. Additionally, a significant difference was found between the experimental and control groups after the intervention (p-value = 0.000). Conclusion: These findings demonstrate that therapeutic communication is effective in reducing patient anxiety during catheterization procedures. This study recommends therapeutic communication as an integral part of nursing services to improve the quality of patient care. This intervention not only reduces anxiety but also contributes to the success of medical procedures.